Kreativitas Guru Memanfaatkan Lingkungan Sekitar Dalam Pembelajaran Tahfidz Alquran - Lisa, Mona; Murniyetti, Murniyetti (Prodi Pendidikan Keagamaan Islam, 2024)
The surrounding environment provides a lot of knowledge and experience for the development of students but not all teachers can realize this. This study aims to determine and analyze the creativity of teachers in utilizing the surrounding environment in learning Quran memorization for fifth-grade students at Buah Hati Padang Integrated Islamic Elementary School. This research uses a qualitative method with a case study approach. Data sources were taken from informants through in-depth interviews consisting of principals, teachers, and students selected using a purposive sampling technique. All interview results were then analyzed systematically using the Milles & Hubberman Interactive Analysis Model technique with the Thematic Analysis method. Overall, the results of the research analysis show that there are three findings in the theme of teacher creativity in utilizing the surrounding environment in learning Quran memorization, namely, i) mosque, ii) Padang State University campus, and iii) beach. The results of this study can be used as evaluation material for teachers and as a determinant for choosing the right method for schools to arouse the enthusiasm of students in learning to memorize the Quran.